INTEGRATING OF LOCAL CULTURE-BASED INSTRUCTION IN TEACHING SPEAKING CLASSROOM AT THE THIRD SEMESTER STUDENTS OF UNIVERSITAS TOMAKAKA MAMUJU - Abdul Rahman R; Syahban Mada Ali; Badriah (Inspiring: English Education Journal, 2022)
This study aims to explore an integration of local culture in teaching speaking for enabling students to speak English practiced in EFL classroom. It employs a descriptive study using a purposive sampling technique and taking 76 respondents from EFL university students. The questionnaire and interview were used to collect data on the perception of EFL university students on the integration of local culture in the process of learning, and observation was applied to gain the data on the EFL students’ interaction on integrating local culture-based instruction. The result of the study shows that students' speaking on the integration of local culture-based instruction in teaching speaking classroom in Indonesian EFL classroom fall into 3 categories:(1) highly understanding of local culture (HULC); (2) moderately understanding of local culture (MULC); (3) low understanding of local culture (LULC). This research is expected to be a reference for teachers’ professional development especially teachers’ capacity in teaching speaking classes.